Analysis of Molding Process Parameters of Bra Cup (Journal of Fiber Bioengineering and Informatics, 2018)
Polyurethane foam is the material most widely used in bra cup production. From the mainfactors affecting the molding process of molded cup, this article analyzed the properties of polyurethanefoam, and elaborated the principle of molding from the molecular structure of polyurethane foam. Then,a set of molding experiments has been done for three different parameters of materials. The results ofthe experiment analyzed the molding process parameters of the polyurethane foam, and summarizedthe main factors affecting the same. The work aims to develop a quantitative control method for bracup modelling process.
Keywords: polyurethane foam; molding principle; molding processing parameters